THE ROLE OF INFORMATION TECHNOLOGY SUPPORT SYSTEM IN PASSENGER INFORMATION ONLINE AT RESERVATION PT. GARUDA INDONESIA - Ita Zakiah; Ir. Rafael A. Gafar (Jurnal Sistem Informasi, 1997)
This thesis is describing about teknologiinformasi role in supporting the system ofpassenger reservation information online at. Garuda Indonesia in its efforts toimprove services particularly in the field of passenger reservation. Informationtechnology is supported by the components of hardware, software, networking, anddesigning a good database so the system can provide informative data. This isintended to allow consumers to obtain fast and accurate information whenever andwherever they make a reservation. The key to success of all of this is the architectureof the system with information technology supported by hardware components,software, brainware, and communication network. Where each component has amaximum reliability, in order to support the reservation information system that isonline real-time. In this regard, the writer is interested to raise the issue of systemicreservation information technology and its relation to reliability (reliability) insupporting the system and improve service to consumers.